Infinitely many sign-changing solutions for a class of biharmonic equation with p-Laplacian and Neumann boundary condition - Sun, F.; Liu, Lishan; Wu, Yong Hong (Elsevier, 2017)
By introducing a subspace of H 2 (O) with constraints ?u?n| ?O =0 and ? O udx=0 and using the Fountain Theorem, we obtain the existence of infinitely many sign-changing high energy solutions for a biharmonic equations with p-Laplacian and Neumann boundary condition.